2018
DOI: 10.31793/1680-1466.2018.23-4.384
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of regeneration of the endothelium at diabetes mellitus

Abstract: Vascular endothelium is the main organ, suffering from diabetes mellitus (DM) and cardiovascular diseases (CVD). In this review, the role of endothelial progenitor cells (EPCs) in the regeneration of the endothelium and in the formation of new blood vessels is considered. Mechanisms of migration and mobilization of EPCs from the bone marrow to the damage zone are described. The analyzed data show that CVD and DM cause the decrease in the number and the disturbance of the function of EPCs. The data on the heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
1
0
1
Order By: Relevance
“…We previously found that diabetic angiopathy is accompanied by an increase in the level of desquamated endothelial cells (CECs) circulating in the blood, commensurate with its severity. 1,2,3,4,5,6,7 In this study, we set ourselves the goal of analyzing the level of CECs in patients with cardiovascular pathology and their relationship with the level of blood pressure and routine clinical indicators.…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that diabetic angiopathy is accompanied by an increase in the level of desquamated endothelial cells (CECs) circulating in the blood, commensurate with its severity. 1,2,3,4,5,6,7 In this study, we set ourselves the goal of analyzing the level of CECs in patients with cardiovascular pathology and their relationship with the level of blood pressure and routine clinical indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Исследования последних лет существенно изменили представления о роли эндотелия сосудов в общем гомеостазе. С тех пор как в 1980 году была открыта способность эндотелия синтезировать оксид азота (NO), стало известно, что эндотелий отвечает за модулирование тонуса сосудов, транспорт веществ в клетки сосудистой стенки, участвует в регуляции поддержания агрегатного состояния крови, проницаемости кровеносных сосудов, ангиогенезе, формировании внеклеточного мат рикса, обеспечивает трофическую и защитную функции по отношению к другим слоям сосудистой стенки и многое другое [5,6].…”
unclassified